Schedule of Classes, Spring 2010 - University of Wisconsin-Milwaukee. Department of Enrollment Services (My University, 2010)
PDF version of the UW-Milwaukee Schedule of Courses for the Spring 2010 term. Includes registration policies and lists of available classes during this term.
Keywords: Academics; Curriculum; Department of Enrollment Services